Distribution pattern of the Microhyla heymonsi group (Anura, Microhylidae) with descriptions of two new species from Vietnam - Van Hoang, Chung; Nguyen, Tao Thien; Phan, Tien Quang; Pham, Cuong The; Ninh, Hoa Thi; Wang, Bin; Jiang, Jianping; Ziegler, Thomas; Nguyen, Truong Quang (European Journal of Taxonomy, 2022)
We provide the first distribution pattern of the Microhyla heymonsi group based on available molecular and morphological data collected from East and Southeast Asia. Our analyses show a high level of genetic diversity in the M. heymonsi group with nine distinct lineages from China, Myanmar, Vietnam, Laos, Malaysia, Thailand, Cambodia, as well as Singapore, and Indonesia. The study also reveals the discovery of two new species in Vietnam, Microhyla hmongorum sp. nov. from Lai Chau Province and Microhyla xodangorum sp. nov. from Kon Tum Province. When comparing the 12S–16S rRNA gene, the genetic divergence between Microhyla xodangorum and other congeners of the Microhyla heymonsi group ranges from 7.5– to 8.9% (M. cf. heymonsi) and approximately 8.4% between the new species and M. heymonsi s. str. from Taiwan, China. The genetic divergence between Microhyla hmongorum and its congeners ranges from 4.5–5.6% (M. cf. heymonsi) to 8.7% (Microhyla xodangorum). These new findings bring the total number of known species in the genus Microhyla to 48 and the recorded species of Microhyla from Vietnam to 14.